2019
DOI: 10.1002/acr.23791
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Physical Activity and Prevention of Cartilage Loss in People With Knee Osteoarthritis: Data From the Osteoarthritis Initiative

Abstract: Objective. To examine the impact of physical activity on cartilage thickness loss in knee osteoarthritis (OA). Methods. A total of 689 participants with radiographic knee OA at baseline (Kellgren/Lawrence grade ≥2) from the Osteoarthritis Initiative completed the Physical Activity Scale for the Elderly (PASE) questionnaires at annual intervals over 4 years. Magnetic resonance imaging-based cartilage thickness change in the medial femorotibial compartment (MFTC) over 4 years was the main outcome. The impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Bricca et al compared quantitative cartilage loss in the medial compartment on MRI over 48 months between 689 subjects with radiographic knee OA from the OAI with low, moderate, and high physical activity assessed using a Physical Activity Scale for the Elderly (PASE) questionnaire. While there was no association between cartilage loss and activity levels for all subjects combined, women with low activity showed greater cartilage loss than women with moderate activity 23 . Zhu et al compared changes in knee osteophyte size on MRI over 30 months in 408 community-dwelling adults from Tasmanian Older Adult Cohort (TASOAC) study with low, moderate, and high physical activity assessed using a pedometer.…”
Section: Physical Activity and Knee Oamentioning
confidence: 59%
“…Bricca et al compared quantitative cartilage loss in the medial compartment on MRI over 48 months between 689 subjects with radiographic knee OA from the OAI with low, moderate, and high physical activity assessed using a Physical Activity Scale for the Elderly (PASE) questionnaire. While there was no association between cartilage loss and activity levels for all subjects combined, women with low activity showed greater cartilage loss than women with moderate activity 23 . Zhu et al compared changes in knee osteophyte size on MRI over 30 months in 408 community-dwelling adults from Tasmanian Older Adult Cohort (TASOAC) study with low, moderate, and high physical activity assessed using a pedometer.…”
Section: Physical Activity and Knee Oamentioning
confidence: 59%
“…32 Other strategies for preventing PTOA It is important to delineate exercises-therapy which targets specific therapeutic goals from physical activities that contribute to overall general health. Recommended levels of general physical activity have been shown to be important for musculoskeletal health 77,105 , controlling adiposity 80 and may be important for cartilage health. 106 The role of medications, intra-articular injections, medications, assistive devices (e.g., braces, and crutches that reduce loss of balance and re-injury or normalize joint loading pattern), diet and other interventions in mitigating the risk of PTOA is unknown.…”
Section: Surgerymentioning
confidence: 99%
“…Another study, reported that, in a subcohort with presence of Heberden nodes (HN), statin users were at substantially lower risk of radiographic JSN progression compared to matched nonusers, whereas in the HN-negative cohort no such relationship was identified 72 . Analysis of the relationship of physical activity and structural progression, defined by medial femorotibial cartilage thickness loss on MRI, suggested that there may be a protective effect of moderate vs low physical activity in women, whereas no significant relationship was seen in men 73 .…”
Section: Inference Of Structural Efficacy From Observational Cohortsmentioning
confidence: 99%